Pengaruh Lingkungan Kerja, Disiplin Kerja, Perilaku Kreatif-Inovatif Terhadap Kinerja Guru - Dedi Hadian (Pusat Penelitian dan Pengabdian Pada Masyarakat (P3M) STIE Pasundan, 2017)
This research aims to determine the effect of Work Environment, Work Discipline, Creative Behavior-Innovative Partially on Teacher Performance. This research was conducted in one of high school in Bandung with sample of 73 teachers through questionnaire, direct observation and interview technique. Variable Work Environment, Work Discipline and Creative Behavior - Innovative functions as independent variable (Independent), while the Performance Teacher variables serve as dependent variable (dependent). To test hypothesis is used path analysis and simple regression by determining level of significance 0,05 with program of SPSS version 20 and Microsoff Excel. Based on this research, the findings are as follows: Total Effect of Work Environment (X1) on Teacher Performance (Y) of 10.2%, Total Effect of Work Discipline (X2) on Teacher Performance (Y) of 17.1%, Total Influence Creative Behavior -Innovative to Teacher Performance (Y) of 61.6%, Total Influence of these three variables of 88.9%. From these results it can be concluded that the influence of Creative-Innovative Behavior in teaching has the greatest effect on Teacher Performance.